Kicking Away the Ladder, Too: Inside Central Banks. Issue 2 (2nd April 2016) - Vernengo, Matías
Abstract: Central banks are evolving institutions. In developed countries, particularly in Britain, central banks were used as instruments of the state to finance government and to promote economic development. However, once they went up the economic ladder, advanced economies kicked it to preclude developing countries from climbing it, too. It is in this context that the modern independent central bank, concerned with inflation targeting alone, which harkens back to the Victorian era, should be interpreted. This paper analyzes the recent evolution of the Argentine central bank in this broad historical perspective.